Conformal Ricci Soliton on 3-dimensional trans-Sasakian manifolds with respect to SVK connection - Acet, B.E.; Akgün, M.A. (Carpathian Mathematical Publications, 2024)
In this study, we adapt the Schouten-van Kampen (SVK) connection on trans-Sasakian 3-manifolds. Then we consider semi-symmetric conditions on trans-Sasakian 3-manifolds with respect to the SVK connection admitting conformal Ricci soliton.